Concentration of Ownership and Profitability of Assets in Employee‑Owned Companies - Matuszewska-Pierzynka, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The main aim of this article is to verify the research hypothesis stating that in most employee-owned companies the growth in concentration of ownership is accompanied by the decrease in profitability of assets. Empirical studies were conducted among 15 employee-owned companies from Mazowieckie voivodeship, which concluded an agreement with the State Treasury in the years 2000–2004 on the basis of data from the National Court Register. The results indicate that in the studied employee-owned companies the correlation relationship between concentration of ownership and profitability of assets was both positive and negative.